The Impact of the Digitalization System for Subsidized Fertilizer Distribution on the Productivity of Rice Farmers in Malang Regency - Waluyo, Teguh Hadi; Arvianti , Eri Yusnita; Santosa , Budi (Jurnal Dinamika Sosial Ekonomi, 2025)
This research analyses the impact of digitalising the subsidised fertiliser distribution system on the productivity of rice farmers in Malang Regency. The research was conducted on 484 rice farmers from 33 sub-districts during the period of August-November 2024. The research results show that digitalisation does not have a significant direct impact on rice productivity. However, digitalisation has a positive effect on farmer satisfaction and technology accessibility. Farmers' satisfaction and technology accessibility have proven to play a significant mediating role in the relationship between digitalisation and productivity. The success of digitalising subsidised fertiliser distribution depends on increasing farmer satisfaction through responsive services and improved technology accessibility. The research recommends optimising the role of agricultural extension workers and increasing the involvement of farmer groups to maximise the benefits of the digital system.